Structural and dynamical investigation of histone H2B in well-hydrated nucleosome core particles by solid-state NMR - Shi, Xiangyan (2023)
H2A-H2B dimer is a key component of nucleosomes and an important player in chromatin biology. Here, we characterized the structure and dynamics of H2B in precipitated nucleosome core particles (NCPs) with a physiologically relevant concentration using solid-state NMR. Our recent investigation of H3-H4 tetramer determined its unique dynamic properties and the present work provides a deeper understanding of the previously observed dynamic networks in NCP that is potentially functionally significant. Nearly complete 13C, 15N assignments were obtained for H2B R30-A121, which permit extracting unprecedented detailed structural and amino-acid site-specific dynamics. The derived structure of H2B in the well-hydrated NCP sample agrees well with that of X-ray crystals. Dynamics at different timescales were determined semi-quantitatively for H2B in a site-specific manner. Particularly, higher millisecond-microsecond dynamics are observed for H2B core regions including partial α1, L1, partial α2, and partial L3. The analysis of these regions in the context of the tertiary structure reveals the clustering of dynamical residues. Overall, this work fills a gap to a complete resonance assignment of all four histones in nucleosomes and delineates that the dynamic networks in NCP extend to H2B, which suggests a potential mechanism to couple histone core with distant DNA to modulate the DNA activities.